2014
DOI: 10.1371/journal.pone.0104736
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Controls Immune and Metabolic Functions during Toxoplasma gondii Infection

Abstract: CCR5, an important receptor related to cell recruitment and inflammation, is expressed during experimental Toxoplasma gondii infection. However, its role in the immunopathology of toxoplasmosis is not clearly defined yet. Thus, we inoculated WT and CCR5-/- mice with a sub lethal dose of the parasite by oral route. CCR5-/- mice were extremely susceptible to infection, presenting higher parasite load and lower tissue expression of IL-12p40, IFN-γ, TNF, IL-6, iNOS, Foxp3, T-bet, GATA-3 and PPARα. Although both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
21
1
1
Order By: Relevance
“…In addition, akin to our situation, there was a similar parasite burden in the small intestine of both animals. Even more surprising, Bonfa et al showed an inverse correlated phenotype where T.gondii ‐infected CCR5 knockout mice displayed increased gut inflammatory lesions but decreased levels of mRNA levels IFNγ and TNFα (and many more cytokines) in the ileum. These studies, including ours, underline the complexity of mechanisms controlling gut inflammation during T. gondii infection and indicate that pathways, unrelated to IFNγ and TNFα, operate during infection and control the intensity of inflammatory gut lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, akin to our situation, there was a similar parasite burden in the small intestine of both animals. Even more surprising, Bonfa et al showed an inverse correlated phenotype where T.gondii ‐infected CCR5 knockout mice displayed increased gut inflammatory lesions but decreased levels of mRNA levels IFNγ and TNFα (and many more cytokines) in the ileum. These studies, including ours, underline the complexity of mechanisms controlling gut inflammation during T. gondii infection and indicate that pathways, unrelated to IFNγ and TNFα, operate during infection and control the intensity of inflammatory gut lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several studies have shown that CCR5 signalling has different and fundamental roles in T. gondii infection. CCR5 participates in processes that contribute to parasite persistence as well as in the host immune response against the parasite (Bonfá et al, 2014; Denkers, 2003; Diana et al, 2005; Golding et al, 2003; Ibrahim, Bannai, Xuan, & Nishikawa, 2009; Khan et al, 2006; Kikumura, Ishikawa, & Norose, 2012; Luangsay et al, 2003; Nishimura, Umeda, Suwa, Furuoka, & Nishikawa, 2017; Scanga et al, 2002). For example, T. gondii can secrete cyclophilin‐18, a chemokine mimic that binds to CCR5, promoting IL‐12 production, which is one of the molecules used by the parasite to modulate the host immune response (Denkers, 2003).…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%
“…For example, T. gondii can secrete cyclophilin‐18, a chemokine mimic that binds to CCR5, promoting IL‐12 production, which is one of the molecules used by the parasite to modulate the host immune response (Denkers, 2003). CCR5 promotes control of T. gondii infection and is important to maintain the metabolic, hepatic and intestinal integrity of the host (Bonfá et al, 2014). Also, CCR5 absence can increase susceptibility to T. gondii (Bonfá et al, 2014; Khan et al, 2006).…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant TgCyp18 has been reported to enhance RANTES expression in macrophages and to control their migration (14,15). CCR5 is essential for controlling infection by T. gondii; CCR5-deficient (CCR5 Ϫ/Ϫ ) mice showed high susceptibility to infection, severe tissue damage, low expression levels of IFN-␥ and IL-12, and high parasite loads compared with wild-type mice (16).…”
mentioning
confidence: 99%